The impact of employing some applications of the second generation of the Web (WEB2.0) on the marketing and development of learning resource center services - Albalushi, Ali Salim Mohammed (Journal of Educational and Psychological Sciences, 2023)
The study dealt with the impact of employing some of the second-generation web applications WEB2.0 on the marketing and development of learning resource centers services. The challenges and obstacles that prevent effective employment, while analyzing this and providing some solutions that may contribute to the effective employment of these applications. -2019 AD, the number of (27) samples, and the descriptive analytical method was used through the interview. The study concluded that the applications of the second generation of the web WEB2.0 are effective in marketing the services and activities of learning resource centers and promoting their effective role and reaching the beneficiary, in addition to that social networks and electronic blogs are of greater use in marketing and developing the services of learning resource centers as a result of the reliance of the learning resource center specialist on The characteristics and advantages of each application in marketing and developing the services provided, and that the weakness of the infrastructure and the lack of skill of some specialists in addition to the lack of programs and courses in the field of employing technology, and the fears of some beneficiaries and their lack of awareness are among the most important challenges and obstacles facing the learning resources specialist in marketing and developing the services provided.
Keywords: WEB2.0 Application; market LRC services; LRC